2014
DOI: 10.4103/0300-1652.128157
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of serum pancreatic amylase and distortion of pancreatic cyto-architecture in type 1 diabetes mellitus rats treated with Ocimum gratissimum

Abstract: Background:Diabetes mellitus has been shown to cause severe impairment in exocrine pancreatic function and cyto-architecture. Ocimum grattissimum has been reported to lower blood glucose levels in experimental diabetic animals. This study, therefore, aims to investigate if treatment with O. grattissimum can alleviate these pancreatic complications of diabetes mellitus. The phytoconstituents and median lethal dose of the plant extract were determined.Materials and Methods:Eighteen rats were divided into three g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…Various scientific studies have shown that N. Laevis possesses antimicrobial, antidiabetic, antioxidant, and antimalarial activities (11)(12)(13)(14). O. gratissimum has been reported to show antidiabetic, antioxidant, anxiolytic, sedative, anti-inflammatory, hepatoprotective, antitumor, gastroprotective, hypolipidemic, insecticidal, nematicidal, and antibacterial activities (4,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Also, scientific reports have revealed that C. papaya possesses immunomodulatory, antimicrobial, anti-inflammatory, antihelmintic, anticancer, wound healing, anti-fertility, abortifacient, diuretic, antihypertensive and antimalarial properties (10,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Various scientific studies have shown that N. Laevis possesses antimicrobial, antidiabetic, antioxidant, and antimalarial activities (11)(12)(13)(14). O. gratissimum has been reported to show antidiabetic, antioxidant, anxiolytic, sedative, anti-inflammatory, hepatoprotective, antitumor, gastroprotective, hypolipidemic, insecticidal, nematicidal, and antibacterial activities (4,5,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). Also, scientific reports have revealed that C. papaya possesses immunomodulatory, antimicrobial, anti-inflammatory, antihelmintic, anticancer, wound healing, anti-fertility, abortifacient, diuretic, antihypertensive and antimalarial properties (10,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…9 Also, there are reports of the use of O. gratissimum to treat upper respiratory tract infections, pneumonia, conjunctivitis and skin diseases. 10 Various scientific studies have identified some of the plant's activities, such as antidiabetic, 11 antioxidant, 12 anxiolytic, 13 sedative, 14 antiinflammatory, 15 hepatoprotective, 16 antitumor, 17 gastroprotective, 18 and hypolipidemic. 19 The antibacterial activity of this plant species has been described in many studies that tested various parts of the plant: extract of leaves, 20 oil from leaves, 21 extract of leaves and stem, 22 oil from aerial parts, 23 and oil from leaves, stem and roots.…”
Section: Introductionmentioning
confidence: 99%
“…Ketoacidosis which is accompanied by severely insufficient insulin action is associated with high level alpha amylase instead of decrease before insulin therapy is initiated [43]. It was however remarked by Akpan and colleagues [44] that the increase in amylase enzyme observed in their study in type 1 diabetes could be a compensatory response triggered in diabetes ketoacidosis. This view was in consonance with previous work in paediatrics by Quiros [45].…”
Section: Discussionmentioning
confidence: 95%